Characteristics of the Colorectal Cancer Microenvironment—Role in Cancer Progression and Therapeutic Possibilities - Paulina Pieniądz; Mateusz Pięt; Roman Paduch (Applied Sciences, 2024)
Colorectal cancer (CRC) is one of the most common and deadliest cancers worldwide. According to the GLOBOCAN (WHO) report in 2020, nearly 2 million patients were diagnosed globally. Despite the advances in cancer diagnosis and therapy, CRC remains a global challenge. Recently, attention has been paid to the tumor microenvironment (TME), which constitutes a significant part of the tumor and mainly includes various immune cells, fibroblasts, vascular cells, and extracellular elements, such as the extracellular matrix (ECM). Many components of the stroma initially exert an anti-tumor effect, but over time, they undergo functional transformation into elements that promote tumor growth. As a result, conditions conducive to further cancer development, invasion into local tissues, and distant metastasis arise. The microenvironment of colorectal cancer (CRC) may be an important direction in the search for therapeutic targets, but it requires further understanding. The main purpose of our review is to explain the role of the complex CRC microenvironment in the progression of this cancer and highlight the potential of targeted therapy directed at the TME. Therefore, continued research into its components and typical biomarkers is necessary to improve therapy and enhance the quality of life for patients.